One-year outcomes of wide antral cryoballoon ablation guided by high-density mapping vs. conventional cryoballoon ablation for atrial fibrillation: a propensity score–matched study - Chen, Sanbao; Wang, Zulu; Xuan, Fengqi; Liang, Ming; Jin, Zhiqing; Ding, Jian; Sun, Mingyu; Zhang, Ping; Han, Yaling (Frontiers in Cardiovascular Medicine, 2024)
Background Pulmonary vein isolation with wide antral ablation leads to better clinical outcomes for the treatment of atrial fibrillation, but the isolation lesion is invisible in conventional cryoballoon ablation. In this study, we aim to investigate the efficacy of the wide pulmonary vein isolation technique that includes the intervenous carina region, guided by high-density mapping, compared with pulmonary vein isolation alone without the mapping system. Methods We conducted a propensity score–matched comparison of 74 patients who underwent a wide cryoballoon ablation guided by high-density mapping (mapping group) and 74 controls who underwent conventional cryoballoon ablation in the same period (no-mapping group). The primary outcome was a clinical recurrence of documented atrial arrhythmias for >30 s during the 1-year follow-up. Results Of 74 patients in the mapping group, residual local potential in the pulmonary vein antrum was found in 30 (40.5%) patients, and additional cryothermal applications were performed to achieve a wide pulmonary vein isolation. Compared with the no-mapping group, the use of the mapping system in the mapping group was associated with a longer fluoroscopic time (26.97 ± 8.07 min vs. 23.76 ± 8.36 min, P = 0.023) and greater fluoroscopic exposure [339 (IQR181–586) mGy vs. 224 (IQR133–409) mGy, P = 0.012]. However, no significant differences between the two groups were found in terms of procedural duration and left atrial dwell time (104.10 ± 18.76 min vs. 102.45 ± 21.01 min, P = 0.619; 83.52 ± 17.01 min vs. 79.59 ± 17.96 min, P = 0.177). The rate of 12-month freedom from clinical atrial arrhythmia recurrence was 85.1% in the mapping group and 70.3% in the no-mapping group (log-rank P = 0.029). Conclusion Voltage and pulmonary vein potential mapping after cryoballoon pulmonary vein isolation can identify residual potential in the pulmonary vein antrum, and additional cryoablation guided by mapping leads to improved freedom from atrial arrhythmias compared with conventional pulmonary vein isolation without the mapping system. Clinical Trial Registration Number ChiCTR2200064383.